2014
DOI: 10.1002/stem.1519
|View full text |Cite
|
Sign up to set email alerts
|

The Subventricular Zone Is Able to Respond to a Demyelinating Lesion After Localized Radiation

Abstract: Radiation is a common tool in the treatment of brain tumors that induces neurological deficits as a side effect. Some of these deficits appear to be related to the impact of radiation on the neurogenic niches, producing a drastic decrease in the proliferative capacity of these regions. In the adult mammalian brain, the subventricular zone (SVZ) of the lateral ventricles is the main neurogenic niche. Neural stem/precursor cells (NSCs) within the SVZ play an important role in brain repair following injuries. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 65 publications
2
33
0
Order By: Relevance
“…This indicates that without gene manipulation, NG21/DCX1 cells are not able to acquire the phenotype of mature neurons, which is in accordance with a study showing a massive appearance of DCX1 cells 3 days after cortical injury, but their complete disappearance 28 days after injury (Susarla et al, 2014). Moreover, it was shown that Dcx is also expressed in NG2 cells (Plane et al, 2012) and in the progenitors that give rise to oligodendrocytes in the subvetricular zone (Capilla-Gonzalez et al, 2014); therefore, we suppose that Dcx is not a specific marker of neuronal progenitor.…”
Section: Shh Controls Production Of Reactive Astrocytes From Ng2 Cellsupporting
confidence: 88%
“…This indicates that without gene manipulation, NG21/DCX1 cells are not able to acquire the phenotype of mature neurons, which is in accordance with a study showing a massive appearance of DCX1 cells 3 days after cortical injury, but their complete disappearance 28 days after injury (Susarla et al, 2014). Moreover, it was shown that Dcx is also expressed in NG2 cells (Plane et al, 2012) and in the progenitors that give rise to oligodendrocytes in the subvetricular zone (Capilla-Gonzalez et al, 2014); therefore, we suppose that Dcx is not a specific marker of neuronal progenitor.…”
Section: Shh Controls Production Of Reactive Astrocytes From Ng2 Cellsupporting
confidence: 88%
“…Hence, the neurogenic system of aged mice becomes a better model for comparisons with adult human beings than the neurogenic system from young rodents. The maintained oligodendrogenesis provides new insight into the relevance of the oligodendrocytes throughout life, which could be a response to myelin damaged during aging (Nait-Oumesmar et al, 1999; Jablonska et al, 2010; Gonzalez-Perez and Alvarez-Buylla, 2011; Capilla-Gonzalez et al, in press). Moreover, oligodendrogenesis could be beneficial for the proper function of the remaining neurons in the aged brain.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblasts in the RMS retain their ability to proliferate (Smith and Luskin, 1998; Poon et al, 2010), but once they reach the OB, neuroblasts begin radial migration and mature into interneurons that integrate in preexisting functional circuits (Lois and Alvarez-Buylla, 1994; Luskin et al, 1997; Carleton et al, 2003; Imayoshi et al, 2008; Kelsch et al, 2010; Lazarini and Lledo, 2011). Although most SVZ precursor cells generate neuroblasts to support OB neurogenesis, a small subpopulation of precursors gives rise to cells in the oligodendroglial lineage, which are able to migrate toward the corpus callosum, striatum, or septum to differentiate into myelinating oligodendrocytes (Nait-Oumesmar et al, 1999; Menn et al, 2006; Gonzalez-Perez et al, 2009; Gonzalez-Perez and Alvarez-Buylla, 2011; Capilla-Gonzalez et al, in press). …”
Section: Introductionmentioning
confidence: 99%
“…Then, neuroblasts move radially and mature into interneurons that integrate in preexisting functional circuits (Lois and Alvarez-Buylla, 1994 ; Lois et al, 1996 ; Luskin et al, 1997 ; Carleton et al, 2003 ; Alvarez-Buylla and Lim, 2004 ; Imayoshi et al, 2008 ; Kelsch et al, 2010 ; Lazarini and Lledo, 2011 ). In rodents, most SVZ precursor cells become neuroblasts to support OB neurogenesis, while a small subpopulation of new cells migrates to periventricular areas such as the corpus callosum or striatum, where they give rise to myelinating oligodendrocytes, both in the normal brain and after demyelinating lesion (Nait-Oumesmar et al, 1999 ; Menn et al, 2006 ; Gonzalez-Perez et al, 2009 ; Capilla-Gonzalez et al, 2014b ).…”
Section: The Subventricular Zone: a Principal Reservoir Of Nscsmentioning
confidence: 99%